Environmental Impact Assessment of Paving Block Production from Plastic Waste Using the Life Cycle Assessment (LCA) Approach - Johari, Harry Irawan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The growing volume of non-commercial plastic waste poses significant environmental challenges while also presenting opportunities for alternative construction materials. This study aims to assess the environmental impacts of producing paving blocks from plastic waste using the Life Cycle Assessment (LCA) approach. A cradle-to-gate system boundary was applied, encompassing five main production stages: sorting, shredding, melting, hydraulic molding, and cooling. Inventory data were collected from daily production activities, with plastic waste inputs ranging from 1.48 to 2.12 tons per day, and paving block outputs of approximately 0.0018 tons per day, along with electricity consumption between 200 and 250 kWh. The results indicate that the extrusion and molding stages contribute most significantly to environmental impacts due to high energy consumption and thermal emissions. Despite the relatively low product output, converting plastic waste into paving blocks contributes to landfill reduction and supports circular economy principles. The study recommends improving energy efficiency and integrating renewable energy sources to further reduce environmental impacts. Overall, the findings demonstrate the potential of plastic waste-based paving blocks as a sustainable innovation for infrastructure development.